Managerial practices and challenges in various economic sectors - Akhmedova, Olena; Antoniuk, Iryna; Bilous, Oleksandr; Burda, Anna; Cherchyk, Larysa; Hrabovska, Iryna; Jarosh, Piotr; Kącicka, Grażyna; Karvatska, Nataliia; Khainskyi, Vadym; Khomiuk, Nataliia; Kozliuk, Vladyslav; et al. (Higher School of Social and Economic in Przeworsk, 2025)
The articles presented in this monograph reflect this spirit of innovation and interdisciplinarity. The structure of the volume – divided into four key chapters: Public Sector Management, Private Sector Management, Social Sector and Non-Governmental Management, and Cross-Sectoral and Interdisciplinary Management Approaches – demonstrates the diversity of approaches and the wide spectrum of topics addressed by the authors. Each contribution provides theoretical insight and practical guidance, offering significant value for enterprise managers, public administrators, researchers, and university students alike.
Keywords: Public sector management; Private sector management; Social sector and non-governmental management; cross-sectoral and interdisciplinary management approaches